New Age Business Model - (:unkn) unknown (ATLAS SkillTech University, 2025)
FYBBA New Age Business Model Question Paper Semester 2
25BB201MBN
First Year Question Paper
Keywords: Business Model; Business; SOCIAL SCIENCES::Business and economics::Business studies